MENYENTUH DAN MENYEMBUHKAN: STUDI TENTANG PRAKTIK KESEMBUHAN YESUS DALAM KRISIS KESEHATAN GALILEA - Ivonne Sandra Sumual (Diegesis : Jurnal Teologi, 2024)
This study examines the theological and practical implications of Jesus’ healing practices, particularly about women’s mental health in Indonesia. Jesus, as a healer in the first century in Galilee, transcended social and religious boundaries by touching and healing those marginalized, including women. The practice of healing through physical touch is not only a medical act but also reflects God’s compassion that touches individuals' physical, emotional, and spiritual aspects. In the Indonesian context, where women’s mental health is often neglected and stigmatized, Jesus’ approach offers a model of ministry that the church can adopt to create an inclusive and supportive environment. This study uses library research methods to analyze theological and historical literature and compares the social conditions in Galilee with women’s mental health in Indonesia. The results show that Jesus’ holistic approach can inspire the church to support the psychological and spiritual well-being of the congregation, as well as address the stigma of mental health, creating broader healing in society.